Towards A Sustainable Urban Community at The Point Development in Durban - Cloete, Magdalena C; Govender, Viloshin (UI Scholars Hub, 2024)
Urban design is the art and method of shaping cities and communities; it plays a pivotal role in creating sustainable, liveable environments that cater to the diverse needs of residents. As urbanization continues to shape our world, integrating architectural education with a bottom-up approach to urban design becomes increasingly imperative. This paper explores the symbiotic relationship between architectural education and urban design, emphasizing the benefits of adopting a bottom-up approach toward creating sustainable urban neighbourhoods. This research aims to explore and understand the role of architectural education and urban design in developing a sustainable urban neighbourhoods in the case study of The Point Precinct in Durban, eThekwini, KZN. A bottom-up approach to urban design places communities at the heart of decision-making processes. Rather than relying solely on top-down, expert-driven solutions, this approach recognizes residents knowledge, aspirations, and needs when aligned with a bottom-up perspective, Architectural education teaches students to be active listeners, keen observers, and empathetic designers. This approach equips future architects with the skills to engage with communities, fostering a sense of ownership and co-creation in urban projects. The theoretical framework combines the concepts of sustainability, urban resilience, and the “right to the city